VISUAL-BASED TRAINING METHOD AND SAFE PRODUCTION PRACTICES IN THE BREWING INDUSTRY IN SOUTHWESTERN NIGERIA (2019)
Managements of breweries in Nigeria always ensure protective and safety measures and standards owing to the unsafe working environment which makes the workers prone to accidents and injuries. Nevertheless, most workers still exhibit work behaviours that expose them to fatalities and accidents. Most of these accidents are avoidable, if the workers are well trained to promote safety and ensure compliance with safety measures using activity-based training methods. Previous studies have focused more on other activity-based methods, such as syndicate training, guided practice, blended learning and role playing, than the visual-based training method. This study, therefore, was designed to determine the effects of visual-based training method on safe production practices (SPP) in the brewing industry in southwestern Nigeria. Moderating effects of job tenure and education level were also examined. Dual-coding and cognitive theories of multimedia learning provided the framework. The mixed method of survey and pretest-posttest control group quasi experimental design of 2x3x3 factorial matrix was adopted. International Breweries PLC, Ilesa (treatment) and Nigerian Breweries PLC, Ibadan (control) were used. Seventy-eight production workers with records of safety negligence were purposively selected and randomly assigned to treatment (46) and control (32) groups. The instruments used were Visual-based Training Guides, SPP Questionnaire (r=0.78) and Knowledge (r=0.74) Attitude (r=0.78) and Management (r=0.77) of Brewing Safe Practices Questionnaire. Four sessions each of key informant and in-depth interviews were held with the human resource/safety managers and safety committees’ representatives/ unit supervisors. Quantitative data were analysed using percentages and Analysis of Covariance at 0.05 level of significance, while qualitative data were content-analysed. The participants were mostly males (74.0%), with 35.6 ±5.13 years of age; and from the brew house (36.3%), engineering (28.8%), packaging (28.2%) and other units (6.7%) on monthly salary of N51,000.00 (64.0%). The majority were permanent workers (92.2%), married (72.9%), first degree (42.4%) and Higher National Diploma holders (46.3%) with long job tenures (73.5%). Treatment had a significant main effect on SPP (F(1;175)=10.22; partial ŋ2=.03). The participants in the treatment group had a higher postmean score (50.63) than those in the control (44.83) group. Job tenure had a significant main effect on SPP (F(2;174)=3.00; partial ŋ2=.03). The participants with long job tenure had the highest postmean score (49.82), compared with those with medium (47.70) and short (47.73) length of service. Education level had a significant main effect on SPP (F(2;174)=3.27; partial ŋ2=.04). The participants that were highly educated had the highest postmean score (49.36) compared with those who were moderately educated (47.97) and less educated (42.86). While the two-way interaction effects were not significant, the three-way interaction effect was significant (F(2;164)=3.32; partial ŋ2= .04). Owing to the nonchallant attitude and use of mobile telephones, most workers did not comply with standard operation procedures, especially when on night shifts. Visual-based training method was effective in promoting safe production practices in the brewing organisations in southwestern Nigeria. Therefore, this training method should be used regularly in inculcating safety measures and compliance in brew staff, particularly those with short job tenures and low education.